Molecular detection of Mycobacterium leprae in the lachrymal film of leprosy cases, health staff, and healthy individuals - Sabage, Josmar; Sabage, Luís E; Belone, Andrea FF; Querino, Gislaine A; Fachim, Luciana R; Pinheiro, Luiza; Virmond, Marcos CL (The Journal of Infection in Developing Countries, 2025)
Introduction: Leprosy is still endemic in some countries, and interruption of the infection chain is essential to reduce its burden. This article aims to verify if the lachrymal film of leprosy cases and non-leprosy can be a site of relevance in the early molecular detection of M. leprae. Methodology: the quantitative polymerase chain reaction technique was used. The sample included 54 patients with leprosy compared to 49 health professionals working at a hospital specialized in leprosy (staff), and 51 healthy individuals outside the hospital without theoretical contact with patients (outsiders). The qPCR was used for the detection of Mycobacterium leprae in lacrimal samples of different clinical forms, where molecular detection was based on the overlap of the Specific Repetitive Element. Results: M. leprae DNA was demonstrated in all three groups in significantly increasing proportions among the outsiders, staff, and patient groups, respectively, 13.7%, 37.8%, and 42.5%. Conclusions: Mycobacterium leprae, in endemic countries, is present in the environment and can transmit to humans, regardless of the determination of the infection process and immune response. Known to be a direct and aerial transmission microorganism, it was also found that M. leprae is present in the tear film, being more prevalent in leprosy cases than in the general population. These findings may have epidemiological repercussions along the disease’s transmission chain.